2014
DOI: 10.1007/978-3-319-02931-3_61
|View full text |Cite
|
Sign up to set email alerts
|

Some Popular Usability Evaluation Techniques for Websites

Abstract: Abstract. Usability is widely considered to be an essential attribute for fulfilling the quality requirements of any software product. In context to web based products especially web sites, usability is the process for making the navigational prospects more user friendly and task effectiveness to meet user's satisfaction. If any website fails to navigate a user to his respective goals, then the user loses his interest and considers it as a less usable website. For simplicity, if any software fails to meet user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Usability is necessary to make the navigational process more friendly and effective to meet users' satisfaction. Precisely, it assists the user to reach his goals and maintain his interest in using the website (Roy & Pattnaik, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Usability is necessary to make the navigational process more friendly and effective to meet users' satisfaction. Precisely, it assists the user to reach his goals and maintain his interest in using the website (Roy & Pattnaik, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…User testing is considered as an important approach in order to identify the problems encountered using a product or a website (Barnum, 2002;Dumas and Redish, 1999). In user testing, users are observed, while they perform the pre-determined tasks related to website (Bastien, 2010;Roy and Pattnaik, 2013). During the tests, users are asked to think aloud and this is an effective technique called "Think Aloud Protocol" to get the verbal feedback of the users (Ericsson and Simon, 1980;Lazar, 2006;Nielsen, 1993).…”
Section: Web Presence and Web Usabilitymentioning
confidence: 99%
“…Questionnaires are useful post-data collection instruments in order to measure the user satisfaction and to obtain the user comments on the system usability (Dumas and Fox, 2009;Roy and Pattnaik, 2013;Rubin and Chisnell, 2008). User satisfaction was accepted as an important indicator for website usability by several studies (Bertot et al, 2006;King and Jannik, 2005;Ferreira and Pithan, 2005;Preece et al, 1994;Roy and Pattnaik, 2013). In accordance with this statement, users are asked to rate the website in the post-questionnaire, after the tasks are completed on that site by the user.…”
Section: Web Presence and Web Usabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Roy and Pattnaik [10] in 2013 have proposed usability evaluation techniques to evaluate the usability of web services based on specific usability attributes. The authors identified two new usability factors namely device independence and provision for physically disabled person in addition to the current attributes which enriches the quality of the web services and increase the global value of the products.…”
Section: Literature Reviewmentioning
confidence: 99%